Respuesta :
remember
(x^m)/(x^n)=x^(m-n)
7^16/6^12=7^(16-12)=6=7^4
so
7^4=7^-18/?
?=7^?
7^4=7^-18/7^?
7^-18/7^?=7^(-18-?)=7^4
-18-?=4
add 18
-?=22
tmes -1
?=-22
7^-22
answer is C
(x^m)/(x^n)=x^(m-n)
7^16/6^12=7^(16-12)=6=7^4
so
7^4=7^-18/?
?=7^?
7^4=7^-18/7^?
7^-18/7^?=7^(-18-?)=7^4
-18-?=4
add 18
-?=22
tmes -1
?=-22
7^-22
answer is C
Answer:
[tex]7^{-22}[/tex]
C is correct.
Step-by-step explanation:
Given: [tex]\dfrac{7^{16}}{7^{12}}=\dfrac{7^{-18}{x}[/tex]
using exponent law:
Product Rule: [tex]x^m\times x^n=x^{m+n}[/tex]
If base is same in multiply add their exponent.
[tex]\dfrac{7^{16}}{7^{12}}=\dfrac{7^{-18}{x}[/tex]
[tex]x=\dfrac{7^{-18}\cdot 7^{12}}{7^{16}}[/tex]
[tex]x=7^{-18+12-16}[/tex]
[tex]x=7^{-22}[/tex]
Hence, At the place of ? is [tex]7^{-22}[/tex]